Detection of Foreign Bodies in Roasted Coffee by using Active Thermography - Ngoensod, A.; Nunak, N.; Suesut, T. (My University, 2017)
This paper presents the detection of foreign bodies in roasted coffee by using active thermography with real-time thermal image processing. Foreign bodies, including stone, wood, etc., are found in roasted coffee beans contaminated during drying process and transportation. The principle of radiation from objects with different emissivity and heat capacity is applied. The heat radiation from the roasted coffee and the foreign body are different; therefore, the thermal image can be used to identify the foreign objects. The active thermography system consists of a thermal image camera and computer image processing, heat source and conveyor system controlled by programmable logic controller. The testing and experimental results of the proposed system show that the foreign bodies in roasted coffee beans can be found in all batches, however, the number counting of foreign objects are inaccurate.
Keywords: Active Thermography; Emissivity; Thermal image processing